2014
DOI: 10.1111/ejn.12669
|View full text |Cite
|
Sign up to set email alerts
|

Testing the role of preBötzinger Complex somatostatin neurons in respiratory and vocal behaviors

Abstract: Identifying neurons essential for the generation of breathing and related behaviors such as vocalization is an important question for human health. The targeted loss of preBötzinger complex (preBötC) glutamatergic neurons, including those that express high levels of somatostatin protein (SST neurons), eliminates normal breathing in adult rats. Whether preBötC SST neurons represent a functionally specialized population is unknown. We tested the effects on respiratory and vocal behaviors of eliminating SST neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 86 publications
(136 reference statements)
1
19
1
Order By: Relevance
“…Alternatively, it may be that input from this group is not required by rhythm generating core of the preBötC, but instead represents a peripheral component of the rhythm generating network. This view is supported by recent work by Tupal et al (), who found that elimination of glutamate release from SSTergic preBötC neurons is not associated with any respiratory phenotype, as would be predicted if this population contained the pacemaking kernel.…”
Section: Discussionsupporting
confidence: 56%
“…Alternatively, it may be that input from this group is not required by rhythm generating core of the preBötC, but instead represents a peripheral component of the rhythm generating network. This view is supported by recent work by Tupal et al (), who found that elimination of glutamate release from SSTergic preBötC neurons is not associated with any respiratory phenotype, as would be predicted if this population contained the pacemaking kernel.…”
Section: Discussionsupporting
confidence: 56%
“…Of these areas, Amb, a motor nucleus, showed high expression of Celf6 protein, yet the decrease in overall vocalization amount seen in the Celf6 mutants did not in any way alter the temporal or spectral features of the remaining calls. This is in contrast to mutations specifically disrupting a brainstem motor circuit (Tupal et al 2014), which resulted in perturbed temporal structure of call phrasing, but a normal overall amount of calls. This argues against the Celf6 −/− phenotype being primarily a result of motoric deficits, and suggests there may be some upstream motivational deficit, despite a loss of the protein in the Amb.…”
Section: Discussionmentioning
confidence: 82%
“…Mammalian vocalization, it should be pointed out, also clearly involves non-Phox2b expressing neurons from XII and phrenic motor pools. Whether the pattern generating premotoneuron populations involved in vocalization are similarly developmentally flexible is an interesting question for future analysis (Bass and Baker, 1997; Bass et al, 2008; Bouvier et al, 2010; Gray et al, 2010; Sweeney and Kelley, 2014; Tupal et al, 2014b). …”
Section: Discussionmentioning
confidence: 99%